The Late Season Butterflies of Koshi Tappu Wildlife Reserve, Eastern Nepal - Khanal, B. (Our Nature, 2007)
Koshi Tappu Wildlife Reserve was explored for butterflies in November, 1999. This was indeed little late for lowland butterflies still brought a list of 54 species categorized under seven families out of 14 families occurring in Nepal. Most of the recorded species in this wetland were common to moderately common in status inhabiting open areas and visitors of water sources and flowers. The altitudinal range and global distribution of each and every recorded species have also been mentioned here. Keywords: Butterflies, Koshi Tappu Wildlife Reserve doi:10.3126/on.v4i1.501 Our Nature Vol.4(1) 2006 pp42-47